International capital market integration, educational choice and economic growth - Hartmut Egger; Peter Egger; Josef Falkinger; Volker Grossmann (Institute for the Study of Labor (IZA), 2005)
This paper examines the impact of capital market integration (CMI) on higher education and economic growth. We take into account that participation in higher education is non-compulsory and depends on individual choice. Integration increases (decreases) the incentives to participate in higher education in capital-importing (-exporting) economies, all other things equal. Increased participation in higher education enhances productivity progress and is accompanied by rising wage inequality. From a national policy point of view, education expenditure should increase after integration of similar economies. Using foreign direct investment (FDI) as a measure for capital flows, we present empirical evidence which largely confirms our main hypothesis: An increase in net capital inflows in response to CMI raises participation in higher education and thereby fosters economic growth. We apply a structural estimation approach to fully track the endogenous mechanisms of the model.
Keywords: F20; H52; J24; O10; 330; capital mobility; capital-skill complementarity; educational choice; education policy; economic growth; wage income inequality; Internationaler Finanzmarkt; Marktintegration; Bildungsverhalten; Studium; Produktivität; Wirtschaftswachstum; Lohnstruktur; Direktinvestition; Schätzung; Theorie; Welt